Can cytoplasmic nucleophosmin be detected by immunocytochemical staining of cell smears in acute myeloid leukemia? - Mattsson, G; Turner, S; Cordell, J; Ferguson, D; Schuh, A; Grimwade, L; Bench, A; Weinberg, O; Marafioti, T; George, T; Arber, D; Erber, W; et al. (2010)
Mutations in the C-terminal region of nucleophosmin in acute myeloid leukemia (AML) result in aberrant cytoplasmic nucleophosmin (cNPM) in leukemic blast cells which is detectable by immunocytochemistry in bone marrow trephine (BMT) biopsy sections. We tested whether cNPM is detectable by immunocytochemistry in air-dried smears of AML with nucleophosmin1 (NPM1) mutations. An immunoalkaline phosphatase method was developed using the OCI-AML3 cell line, known to have mutated NPM1, and assessed on blood and marrow smears of 60 AML cases. NPM was detectable in all blast cell nucleoli and cNPM in 21 of 31 of NPM1 mutated and 15 of 29 wild-type cases. Paired air-dried smears and BMT biopsies from the same case (mutated and wild-type) gave discrepancies in cNPM expression and there was no correlation in 10 of 22 cases. Due to the high false positive and negative rates for cNPM in cell smears, this method should not be used as a surrogate for NPM1 mutations in AML.